Breast cancer in Mexican women: an epidemiological study with cervical cancer control Câncer de mama em mulheres mexicanas: estudo epidemiológico com controles de câncer cervical - Víctor Tovar-Guzmán; Carlos Hernández-Girón; Eduardo Lazcano-Ponce; Isabelle Romieu; Mauricio Hernández Avila (Universidade de São Paulo, 2000)
INTRODUCTION: In Mexico, breast cancer (BC) is one of the main causes of cancer deaths in women, with increasing incidence and mortality in recent years. Therefore, the aim of the study is identify possible risk factors related to BC. METHODS: An epidemiological study of hospital cases of BC and controls with cervical uterine cancer (CUCA) was carried out at eight third level concentration hospitals in Mexico City. The total of 353 incident cases of BC and 630 controls with CUCA were identified among women younger than 75 years who had been residents of the metropolitan area of Mexico City for at least one year. Diagnosis was confirmed histologically in both groups. Variables were analyzed according to biological and statistical plausibility criteria. Univariate, bivariate and multivariate analyses were carried out. Cases and controls were stratified according to the menopausal hormonal status (pre and post menopause). RESULTS: The factors associated with BC were: higher socioeconomic level (OR= 2.77; 95%CI = 1.77 - 4.35); early menarche (OR= 1.32; 95%CI= 0.88 - 2.00); old age at first pregnancy (>31 years: OR= 5.49; 95%CI= 2.16 - 13.98) and a family history of BC (OR= 4.76; 95% CI= 2.10 - 10.79). In contrast, an increase in the duration of the breastfeeding period was a protective factor (>25 months: OR= 0.38; 95%CI= 0.20 - 0.70). CONCLUSIONS: This study contributes to the identification of risk factors for BC described in the international literature, in the population of Mexican women. Breastfeeding appears to play an important role in protecting women from BC. Because of changes in women`s lifestyles, lactation is decreasing in Mexico, and young women tend not to breastfeed or to shorten the duration of lactation. OBJETIVO: O câncer de mama (CM) é uma das principais causas de morte por câncer em mulheres, no México, com aumento da incidência e da mortalidade nos últimos anos. O estudo realizado objetivou identificar possíveis fatores de risco relacionados ao CM. MÉTODOS: Realizou-se um estudo epidemiológico de casos hospitalares de CM e de controles hospitalares com câncer cérvico-uterino (CACU) em oito hospitais de terceiro nível, na Cidade do México. Foram estudados 353 casos incidentes de CM e 630 controles com CACU, identificados entre mulheres com menos de 75 anos de idade, residentes na área metropolitana da Cidade do México pelo menos há um ano. O diagnóstico foi confirmado histologicamente em ambos os grupos. As variáveis foram analisadas de acordo com critérios aprovados biológica e estatisticamente. Foram efetuadas análises univariadas, bivariadas e multivariadas. Os casos e controles foram estratificados de acordo com o estado hormonal menopáusico (pré e pós-menopausa). Foi usado o odds ratio (OR) como método de associação com intervalos de confiança (IC) acima de 95%. RESULTADOS: Os fatores associados com o CM foram: nível socioeconômico alto (OR=2,77 IC 95% 1,77 -- 4,35); menarca prematura (OR=1,32 IC 95% 0,88 -- 2,00); idade acima de 31 anos quando da primeira gravidez (OR=5,49 IC 95% 21,16 -- 13,98) e um histórico familiar de CM (OR=4,76 IC 95% 2,10 -- 10,79). Por outro lado, um aumento na duração da amamentação foi um fator protetor (> 25 meses OR=0,38 IC 95% 0,20 -- 0,77). CONCLUSÕES: Os resultados contribuíram para a identificação de fatores de risco para o CM descritos na literatura internacional na população de mulheres mexicanas. A amamentação parece exercer importante papel na proteção do CM. Em virtude das mudanças no estilo de vida das mulheres, as mulheres jovens tendem a diminuir seu período de amamentação.